Diagnostic Reference Levels in pediatric interventional cardiology: A multicenter study by the French cohort in HARMONIC project - Bouchra Habib Geryes; Soline Bondet De La Bernardie; Sébastien Hascoet; Charlotte Geant; Claire Dauphin; Stéphanie Douchin; Julia Rousseau; François Godart; Valérie Pontvianne; Caroline Ovaert Reggio; Bruno Lefort; Aurore Danvin; et al. (PLoS ONE, 2025)
Background Pediatric interventional cardiology (IC) is an important diagnostic and therapeutic approach for addressing congenital heart disease (CHD) in children. However, the associated ionizing radiation raises long-term health concerns, emphasizing the need for dose optimization. Purpose To establish multicenter diagnostic reference levels (DRLs) for pediatric IC procedures within the French COCCINELLE cohort as part of the HARMONIC European project, providing data to optimize radiation exposure. Methods A retrospective analysis of radiation dose metrics was conducted on pediatric IC procedures performed across seven hospitals from 2018 to 2020. Data were stratified by five weight groups (<5, 5– < 15, 15– < 30, 30– < 50, 50– < 80 kg) and seven IC procedure categories. Median and 75th quantile values for dose-area product (DAP), DAP normalized to body-weight (DAP/BW) and fluoroscopy time (FT) were calculated to define typical values and DRLs, respectively. The DRL-weight curve approach was also used to determine the 50th quantile curve for each IC procedure category. Results A total of 1815 pediatric IC procedures were analyzed, comprising 534 diagnostic and 1281 therapeutic procedures. Significant variations in DAP were observed across different procedure types and weight groups, while fluoroscopy time showed no significant variation. Typical-DRL values (median-75th percentile values) of DAP (Gy·cm²) ranged from 1.9–3.9 to 4.8–5.8 for coronarography, from 0.7–1.3 to 9.2–15.6 for angiography, from 0.3–0.6 to 0.8–1.5 for pulmonary valve dilatation, from 2.8–3.7 to 11.6–14.6 for pulmonary artery dilatation and stenting, from 0.6–1.3 to 2.8–6.0 for atrial septal defect closure and from 0.1–0.4 to 3.1–5.4 for patent ductus arteriosus closure in function of weight groups and 0.2–0.3 for Rashkind in patients <5 kg. Conclusion This study provides the first multicenter DRLs for pediatric IC procedures in France, offering valuable benchmarks for dose optimization. These findings lay a strong foundation for future national and international guidelines in pediatric IC care.